GAMBARAN PENYULUHAN DENGAN MEDIA POSTER DAN ANIMASI TERHADAP PENGETAHUAN TENTANG PEMELIHARAAN KESEHATAN GIGI PADA SISWA/I KELAS IV SDN 050736 PULAU BANYAK KECAMATAN TANJUNG PURA - yetti Lusiani; M Afdal Ridha (Poltekkes Kemenkes Medan, 2019)
Counseling is an effort to provide information and explanations, which must be taken by everyone so thatthey can solve the problems they face and improve the quality of life. To facilitate counseling activities,mediais needed. Media is an effort that can be used to channel messages from senders to recipients so that they canstimulate thoughts, feelings, attention and interests in maintaining optimal health. This study aims todetermine the description of counseling with poster and animation media on knowledge about dental healthcare in fourth grade students of SDN 050736 Pulau Banyak, Tanjung Pura sub district, amounting to 30peoples with a total sample of 30 students. The type of research used was descriptive with the survey method.The results of this study found that the level of knowledge of students about maintaining dental health beforecounseling with poster and animation media, namely 23 peoples (76.6%) were in the medium category. Thenafter counseling the level of knowledge of students about maintaining dental health with media posters has agood level of knowledge there were 8 students (53.3%) and with animation media have good level ofknowledge, there were 15 students (100%). Based on this research, it can be seen that counseling usinganimation media was more effective than using poster media.